THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY ON FIRM PERFORMANCE WITH MANAGERIAL OWNERSHIP AS A MODERATING VARIABLE - Angeline, Viola; Herwiyanti, Eliada; Kusumastati, Widyahayu W.; Setyorini, Christina Tri (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
This study aims to analyze the effect of Corporate Social Responsibility on company performance with managerial ownership as a moderating variable. The research population is insurance and reinsurance companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The total sample used was 13 insurance companies and 1 reinsurance company. The sampling technique uses a non-probability sampling technique using all members of the population as the research sample. The data analysis technique used in this study is multiple regression analysis. The results of this study indicate that: (1) Corporate Social Responsibility has no positive effect on company performance; (2) Managerial ownership has a positive effect on company performance; (3) Managerial ownership does not moderate the relationship between Corporate Social Responsibility and company performance.